Fatal splenic rupture in Ehlers-Danlos syndrome. Issue 713 (March 1985) - Harris, S. C.; Slater, D. N.; Austin, C. A.
Abstract : A fatal case of Ehlers-Danlos syndrome (Type IV) is described. Autopsy revealed splenic rupture that had resulted from spontaneous haemorrhage into the splenic parenchyma. This is a previously unrecorded complication of Ehlers-Danlos syndrome and should be considered in the differential diagnosis of chest and abdominal pain in patients with this condition.